Use of Arabinogalactan Protein in Coconut (Cocos Nucifera L.) Tissue Culture: An Alternative Approach for Improved Tissue Response - Fernando, S. C.; Samarajeewa, D. A. D. S.; Liyanagedara, L. G. N. H. K. (International Coconut Community, 2011)
Arabinogalactan proteins (AGPs) are extra-cellular proteins involved in plant growth and development. The effects of these proteins on in vitro response of different species are well documented. This study assessed for the first time the role of AGPs on tissue culture of coconut, a highly recalcitrant species in vitro. Coconut (Sri Lanka Tall) plumules were cultured in medium containing 2, 4-dichlorophenoxyaceticacid (2,4-D) for callogenesis. Calli were multiplied by subculturing onto freshly prepared callusing medium. Somatic embryos were induced by transferring of calli to medium with 2/3 concentration of initial 2,4-D and matured by subsequent transferring to medium without any hormones. Embryos were converted in the presence of gibberelic acid. Arabic gum (1-50 mgL-1) was used as the main source of AGP. Alternatively, different AGP sources like Larch wood gum, carrot seeds and defatted coconut kernel were also assessed. Arabic gum in callusing medium resulted in early callogenesis from 20-40% plumules compared to 10% in the control. However, it did not have a significant effect on final callusing efficiency. Its presence in somatic embryogenesis medium showed a significantly higher mass of embryogenic structures per an embryogenic clump (33.3-50.5mg) when compared to the control (26.9mg).The best result was obtained at 10mgL-1 Arabic gum. All AGP sources except Larch wood gum had positive effects on somatic embryogenesis. Among them, defatted coconut kernel (25-50mgL-1) showed the best results giving 70% cultures with embryogenic structures compared to 37% in control. However, so far, the positive effect of AGP did not reflect in plant regeneration efficiency.